Decision Support System for Selecting Students to Follow Biological Science Olympiad Using Simple Multi Attribute Rating Technique (SMART) Method - Basrie; Ekawati Yulsilviana (TEPIAN, 2020)
Decision Support System (SPK) is a system that can help someone in making decisions that are accurate and right on target. many problems can be solved by using SPK, one of which is the Decision Support System for Student Selection to Participate in the Biology Science Olympiad with Method (Simple Multi-Attribute Rating Technique). The purpose of this research is to produce a Decision Support System for Student Selection to Participate in the Biology Science Olympiad with the Method (Simple Multi-Attribute Rating Technique), with the hope of selecting students to objectively participate in the National Science Olympiad. By using the Visual Basic.Net programming language and the database used is MySql. In this research, data collection techniques used are observation library studies and interviews. The results of this study are made a decision support system to participate in the Biology Science Olympiad with the Method (Simple Multi-Attribute Rating Technique) after the decision is obtained, the system will display the decision.